Type I interferon subtypes differentially activate the anti-leukaemic function of natural killer cells - Barnes, Samantha A.; Audsley, Katherine M.; Newnes, Hannah V.; Fernandez, Sonia; de Jong, Emma; Waithman, Jason; Foley, Bree (Frontiers in Immunology, 2022)
Natural killer (NK) cells have an intrinsic ability to detect and eliminate leukaemic cells. Cellular therapies using cytokine-activated NK cells have emerged as promising treatments for patients with advanced leukaemia. However, not all patients respond to current NK cell therapies, and thus improvements in efficacy are required. Type I interferons (IFN-I) are a family of potent immunomodulatory cytokines with a known ability to modulate NK cell responses against cancer. Although the human IFN-I family comprises 16 distinct subtypes, only IFNα2 has been widely explored as an anti-cancer agent. Here, we investigated the individual immunomodulatory effects each IFNα subtype and IFNβ had on NK cell functionality to determine whether a particular subtype confers enhanced effector activity against leukaemia. Importantly, IFNα14 and IFNβ were identified as superior activators of NK cell effector function in vitro. To test the ability of these subtypes to enhance NK cell activity in vivo, IFN-I stimulation was overlaid onto a standard ex vivo expansion protocol to generate NK cells for adoptive cell therapy. Interestingly, infusion of NK cells pre-activated with IFNα14, but not IFNβ, significantly prolonged survival in a preclinical model of leukaemia compared to NK cells expanded without IFN-I. Collectively, these results highlight the diverse immunomodulatory potencies of individual IFN-I subtypes and support further investigation into the use of IFNα14 to favourably modulate NK cells against leukaemia.